Implementasi Enterprise Resource Planning Pada Perusahaan Transportasi PT. Xyz - Gidion Aryo Nugraha Pongdatu; Rifqi Fahrudin (Infinity, 2021)
PT. Xyz is a service company engaged in inter-city and provincial transportation that is domiciled in the cities of Cirebon, Bandung, Bekasi and Sukabumi. As a transportation service provider company, PT. Xyz needs an integrated information system in the management effort to support the achievement of company goals. The use of ERP makes all systems in a company into one integrated system, so that several departments become easier to share data, and also easier to communicate. In its development, this company uses an Android-based application to connect companies with customers.